(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Despite the extensive use of modern radiation imaging technologies in neurosurgical practice, the diagnosis and treatment of various brain tumors (BT) remain a challenge for clinicians and healthcare administrators. This is attributed to the high prevalence of primary and secondary brain tumors, the significant number of adverse outcomes, and the substantial costs associated with their treatment.